PichArt Application and Remove Background in SLB Tunas Kasih Surabaya - Camelia, Ika Anggun; Djatiprambudi, Djuli; Ruci, Wening Hesti Nawa; Siregar, Pungki; Putra, Awal; Sampurno, M. Bayu Tejo (Proceeding of International Joint Conference on UNESA, 2025)
Graphic design learning has an important role in developing student creativity, including students with special needs at the Tunas Kasih Special School (SLB) Surabaya. This research aims to implement the PichART application as a learning medium in making posters, especially in the remove background feature, for SLB Tunas Kasih Surabaya students. The PichART application was chosen because of its ease of use and various features that support student creativity. The method used is an experimental study with a practical approach where students are given tutorials and direct practice using the application. The research results show that using PichART can improve students' abilities in poster design, especially in using the remove background feature. In addition, students showed increased learning motivation and creativity in completing design assignments. This research concludes that PichART can be an effective learning tool in supporting the teaching of graphic design for students with special needs, and is able to facilitate them to be more independent and creative in their work.